UNKNOWN AND INTERPRETED: EXPLORING THE NEED TO REPRESENT, UNDERSTAND AND RESPOND - Dan Paich, Slobodan (Journal of Tourism, Sustainability and Well-being, 2018)
Interpreting Past as one of the basic human traits is the main thread of this paper. Addressing communication delivery of meaning, usage and construction methods of Cultural Landmarks within tourism phenomenon that provides information and knowledge to everyone, regardless of their schooling level and qualifications. Chosen examples and issues explored: Embodying Cultural Reference - Canopus of Emperor Hadrian’s Villa at Tivoli near Rome Adoptive Reconstruction - Teatro Olimpico Palladio’s Renaissance performance space in Vicenza inspired by ancient Roman architect Vitruvius’ treaties on theatre construction. Shared Intentions and Structural Expressions - Hattusha - Cumae: Striking programmatic and tectonic similarity and documentary evidence that help comparative understanding and interpretation of both heritage sites. Tangible - Intangible Heritage - Omphalos / Naval of the world: Mediterranean stone markers at ancient oracle sites and possible ritual use of specially trained birds. The closing statements reflect on the culture, needs and psychological underpinnings of the tourism phenomenon as wonder experiences. The seven wonders of the Greco-Roman world exemplify the out of the ordinary character of major heritage sites. Strategies of interpretation that acknowledge and attempt to understand the original building and placing motivations can enrich the experiences of contemporary visitors.